Processo de oxidação eletrolítica a plasma (PEO) como alternativa para remediação de microplásticos - Rodrigues, Lorena Alves (Universidade Federal de São Carlos, 2023)
The world broke its plastics production record in 2021. In this topic, microplastics (PM) have recently become one of the top four global environmental problems due to their abundance in terrestrial environments and aquatic and toxic potential for nature. Because it is omnipresent, the degradation and remediation of this material is a concern that has been taking place in the scientific community in the development of chemical techniques, in particular, the Advanced Oxidative Processes (AOPs). In the present work, the plasma electrolytic oxidation (PEO) process was used in an attempt to remediate polypropylene (PP) and blue ink (PT) microplastics. Aluminum electrodes (98,7%) immersed in an electrolytic solution of 0.1 mol/L Sodium Silicate containing approximately 0.15 g of microplastics were used. The process occurred under constant stirring on a magnetic stirrer and a current density set at 20 mA/cm2 for 90 minutes. Micrographs and compositional analysis data were used through EDS, obtained by the Scanning Electron Microscope and images from the Optical Microscope to analyze the change in the surface of the microplastics and electrodes. An analysis of the electrolytes before and after the PEO process was also performed using Fourier Transform Infrared Spectroscopy (FTIR) to identify whether particles or other substances were moved from the PM to the electrolytic medium. The results suggested alterations in the surface of the microplastics. However, from the view of the results, it is not possible to affirm that the PEO process caused any alteration or if these are interferences only of the physical parameters (temperature, agitation, filtration). However, when analyzing the surface of the oxide formed on the electrodes, inorganic carbon was found, suggesting that this was formed from the treatments carried out in contact with the PP and PT samples. Despite the interaction between PM and electrode, it was not possible to identify, from the FTIR analysis curves, significant changes in the electrolyte by the PEO process with the samples.
Plasma electrolytic oxidation (PEO) process as an alternative for microplastic remediation
Keywords: Remediation; Remediação; Microplásticos; Microplastics; Plastics; Plásticos; Oxidação eletrolítica a plasma (PEO); Plasma Electrolytic Oxidation (PEO); CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA